THE IMPORTANCE OF PRESCHOOL EDUCATION: BUILDING A STRONG FOUNDATION FOR LIFELONG LEARNING - Salamova Feruza Khakimbekovna (Academia Science Repository, 2023)
This article explores the significance of preschool education in shaping a child's overall development. It highlights the benefits of preschool in fostering early brain development, cognitive skills, social and emotional development, language and communication skills, and preparing children for formal education. The article also emphasizes the importance of creativity, imagination, and play in preschool, as well as the holistic approach to child development. It concludes by discussing the role of parental involvement, the promotion of inclusion and diversity, and the long-term benefits of preschool education.